2021
DOI: 10.1177/03009858211045441
|View full text |Cite
|
Sign up to set email alerts
|

Renal epitheliotropism of feline morbillivirus in two cats

Abstract: The association of feline morbillivirus (FeMV) with kidney disease in cats is controversial. Two cats with a history of severe hematuria had eosinophilic inclusion-like bodies in the renal tubular epithelial cells, without any inflammatory cellular reaction. Ultrastructurally, aggregations of electron-dense viral-like particles were found where the inclusion-like bodies were located. Immunohistochemistry (IHC) using antibodies against FeMV matrix protein labeled these inclusion-like bodies, and also labeled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
5
22
0
Order By: Relevance
“…At necropsy, we detected rFeMV US5 in the renal medullary tubule epithelium by IHC and corroborated this by detecting RNA in a serial section. This detection is in good agreement with analysis of kidney sections from naturally infected cats, where the FeMV antigen was detected in renal tubular cells ( 1 , 61 , 65 ). It has also been previously shown that feline primary kidney cells are susceptible to FeMV and that epithelial cells are the primary target ( 35 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At necropsy, we detected rFeMV US5 in the renal medullary tubule epithelium by IHC and corroborated this by detecting RNA in a serial section. This detection is in good agreement with analysis of kidney sections from naturally infected cats, where the FeMV antigen was detected in renal tubular cells ( 1 , 61 , 65 ). It has also been previously shown that feline primary kidney cells are susceptible to FeMV and that epithelial cells are the primary target ( 35 ).…”
Section: Discussionsupporting
confidence: 87%
“…S7 ). IHC performed on lymph node sections from naturally infected FeMV + cats also identified infected macrophages ( 1 , 61 ). It has previously been shown that feline primary pulmonary epithelial cells are susceptible to a closely related FeMV in vitro ( 35 ).…”
Section: Discussionmentioning
confidence: 95%
“…In summary, the urinary tract seems to be an important site for viral replication and persistence, although we cannot exclude replication in other organs, as viral RNA was also detected in the spleen and the liver. This assumption is also supported by a recent study showing FeMV antigen localization in the spleen and the urinary bladder of naturally infected cats [ 19 ]. In addition, Chaiyasak and colleagues demonstrated deposit of FeMV antigens in the urinary bladder, tracheal, and bronchiolar epithelial cells, lymphocytes and macrophages from spleen and mesenteric lymph node as well as in astro- and oligodendroglia in the brain of two naturally infected cats [ 19 ].…”
Section: Discussionsupporting
confidence: 69%
“…The link between FeMV infection and CKD has not been proven yet, but suggested by several observations: (i) a prevalence of 6.1% in urine and 40% (4/10) in kidney tissues of cats with nephritis [ 2 ], (ii) a prevalence of 6.7% (8/120) in cats with signs of urinary tract disease in contrast to no viral detection in healthy cats ( n = 86) [ 4 ], (iii) a high correlation (90%, 26/29) between inflammatory renal lesions and FeMV infection in comparison to non-infected cats (62%, 44/71) [ 12 ], and (iv) a significant association between the presence of FeMV antigen and morphologic tubular and interstitial alterations in cat kidneys [ 13 ]. Recently, histopathological examination of two cats naturally infected with FeMV showed diffuse renal tubular vacuolation with multifocal membranous glomerulo-nephropathy and multifocal necrotizing hemorrhagic cystitis [ 19 ]. Furthermore, the same study showed histological evidence of FeMV matrix protein presence and pathologic changes in lungs, brain, liver, and gastro-intestinal organs.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, after deparaffinization and rehydration of the 4-µm sections, the antigen was unmasked by incubating it in citrate buffer, pH 6, at 95 • C for 20 min, subsequently blocking the endogenous enzyme activity using 3% (v/v) hydrogen peroxide at room temperature for 15 min. The slides were then incubated with each primary antibody targeting Olig-2 (polyclonal rabbit, anti-mouse Olig-2 antibody; Novus Biologicals, CO, USA), GFAP (monoclonal mouse anti-GFAP; Sigma-Aldrich, MO, USA), Iba-1 (monoclonal mouse anti-human Iba-1/AIF1; Sigma-Aldrich) and NeuN (monoclonal rabbit anti-NeuN; Sigma-Aldrich) at specific concentrations, as described previously, at 37 • C for 1 h (Chaiyasak et al, 2021;Pratakpiriya et al, 2017). The slides were incubated with an immuno-alkaline-phosphatase polymer-conjugated anti-mouse antibody (Histofine® simple stain AP [MULTI]; Nichirei, Japan) as a secondary antibody, and positive conjugational signals were visualized using Vector® Blue Substrate Kit-AP (Vector, CA, USA).…”
Section: Dual Ish and Immunohistochemistrymentioning
confidence: 99%